Human adaptation to climate change in the context of forests: a systematic review - Paige Fischer, Alexandra; Aminur Rahman Shah, Mohammad; Segnon, Alcade Christel; Matavel, Custodio; Antwi-Agyei, Philip; Shang, Yuanyuan; Muir, Maegan; Kaufmann, Rachel; The Global Adaptation Mapping Team (Elsevier, 2024)
We assessed how people adapt to climate change in the context of forests through a systematic review of the international empirical research literature. We found that drought, precipitation variability, extreme precipitation and flooding, and extreme heat were the climatic stressors to which responses were most frequently documented. Individuals and households received the most research attention, followed by national government, civil society, and local government. Europe and North America were the geographic foci of more research than other regions. Behavioral responses were more reported than technical and infrastructural responses and institutional responses. Within these types of responses, actors used a wide variety of practices such as replanting, altering species composition, and adopting or changing technology. Adaptation efforts in early planning and advanced implementation received some attention, but early implementation and expanding implementation were most reported. While connections between responses and risk reduction were discussed, there is limited evidence of risk reduction. Our review contributes to the scholarly and practical understanding of how people adapt to climate change in the context of forests. The review also identifies opportunities for future research on adaptation to other climatic stressors, such as wildfires and tree pests and pathogens, adaptation in other geographic areas, especially Oceania, and adaptation by actors beyond the individual and household level and through institutional adaptation efforts.